Innovation Utilizing AI-Based Virtual Assistants for Employee Training and Development - Tri Cicik Wijayanti; Aditya Dandy Firatama; M Jamal Abdul Nasir; Aji Saptaji (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2026)
This study examines the effectiveness of using AI-based virtual assistants in employee training and development. Employing a quantitative approach, data were collected through an online survey of 150 respondents working in various companies in Gresik Regency. The study aims to evaluate employees' perceptions of AI-based virtual assistants, focusing on their effectiveness, ease of use, learning experience, motivation, and impact on skill enhancement and productivity. Descriptive analysis revealed positive perceptions across all measured aspects, with average Likert scale scores above 4.0, indicating strong acceptance of thistechnology. Pearson correlation analysis showed significant positive relationships among the variables, suggesting that a positive perception of one aspect correlates with positive perceptions of others. Multiple linear regression analysis identified